IMPROVEMENT OF THE INSTITUTIONAL ENVIRONMENT FOR THE INNOVATIVE DEVELOPMENT OF AGRICULTURAL ENTERPRISES - SURKOVA, Viktoria (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The role of the state management sector is essential for creating a favorable institutional environment for the innovative development of business entities. The state, thanks to the performance of its inherent functions, stimulates or discourages innovative activity, which is reflected in the pace of economic development and the speed of the transition of the national economy to a new technological system. Institutional provision and support of the GDR and innovative development of the national economy is the exclusive prerogative of the state, whose function includes creating conditions for a favorable investment climate, commercialization of innovations, and motivation of innovative product developers. Innovative development is a complex, multifaceted and dynamic category of economic science, which is the main prerequisite for ensuring the appropriate level of competitiveness of products and enterprises, integration of the domestic economy into the world, sustainable development of the national economy in conditions of worsening social contradictions and increasing man-made load on the ecological environment. The agrarian sphere is exclusively important for achieving the goals and objectives of sustainable development both in the national dimension of the economy of Ukraine and in the global world scale. According to the proposed author’s approach, the architecture of the institutional environment for increasing the innovative activity of agricultural enterprises is based on an organic combination of fundamental state institutions (legal, social, economic, ecological) with institutions whose action should be ensured by market mechanisms. Creation of stimulating prerequisites and financial support of the GDR is an indispensable factor in attracting investment flows to the national economy. The conducted research and practical experience of the functioning and development of the agar sphere made it possible to establish that the institutional support for innovative activity in this sphere is at the stage of development and improvement. The article examines the institutional foundations of the formation of a favorable environment for the introduction of innovations for enterprises in the agrarian sphere. Considerable weight is given to the issue of understanding the architecture of the institutional environment of agricultural enterprises